Antimicrobial activity of Boesenbergia rotunda (L.) Mansf. A. Extract against multi-antibiotics resistant foodborne pathogens - Mohd Zainin, Nurul Syazwani (2015)
Evolution of resistance in foodborne pathogens to the currently available antibiotics in the market demonstrate the importance of identifying novel antimicrobial agent. Therefore, in this study, Boesenbergia rotunda (fingerroot) from Zingiberaceae family was chosen to be further assessed as antimicrobial agent against eight species of reference foodborne pathogens including its multi-antibiotics resistant isolates, namely Escherichia coli, Bacillus cereus, Klebsiella pneumoniae, Listeria monocytogenes, Salmonella spp., Staphylococcus aureus, Vibrio parahaemolyticus and Candida albicans. B. rotunda methanolic extract showed antimicrobial activity against the microorganisms tested. The ranges of MIC and MBC obtained showed that B. rotunda extract had strong antimicrobial activity against V. parahaemolyticus, B. cereus and S. aureus KCCM 12255 with 9.77 – 312.5 µg/ml and 9.77 – 625 µg/ml, respectively. Meanwhile, the B. rotunda extract was least active against L. monocytogenes, Salmonella spp. and C. albicans with MIC values range were 1250 – 5000 µg/ml and MBC/MFC values range were 2500 - >5000 µg/ml. E. coli and K. pneumoniae showed wide range of inhibition and bactericidal concentrations which were 19.53 – 2500 µg/ml and 39.06 – 5000 µg/ml, respectively. The time-kill curves demonstrated that B. rotunda extract can kill the microorganisms tested with more than 3 log10 (99.99%) within 0.5 to 4 hours of incubation with bactericidal endpoints for B. cereus, V. parahaemolyticus, E. coli ATCC 25922 and S. aureus KCCM 12255 were from 78.13 – 1250 µg/ml (2 MIC and 4 MIC), whereas the bactericidal/fungicidal endpoints for isolated E. coli O157:H7, K. pneumoniae, L. monocytogenes, Salmonella spp. including C. albicans ATCC 14503 were from 2500 – 5000 µg/ml (2 MIC, 4 MIC, and 8 MIC). Generally, the antimicrobial activities of B. rotunda extract were not significantly affected by pH (3, 7, and 11) and temperatures (30˚C, 50˚C, 80˚C and 121˚C). Natural microflora in fruit and vegetable samples also can be reduced at least by 2 log10 CFU/g after treatment with 0.05% (0.5 mg/ml), 0.5% (5 mg/ml) and 5% (50 mg/ml) of B. rotunda extract. Among these treatment solutions, the relative best combination between antimicrobial ability and sensory acceptability can be achieved with 0.05% (0.5 mg/ml) B. rotunda extract, where it showed a significant bacterial population reduction as well as high mean score for the tested sensory attributes. The B. rotunda extract was found not to be toxic with LC50 more than 1.0 mg/ml. GC-MS analysis showed that the antimicrobial properties of the extract possibly attributed by major bioactive compounds, namely camphor, geraniol, methyl cinnamate, pinocembrin and pinostrobin chalcone. It can be concluded that B. rotunda extract has a potential as antimicrobial agent against multi-antibiotics resistant foodborne pathogens which deserves further investigation for development of natural food sanitizer.